Pedagogi Profetik Di Era Disrupsi: Rekonstruksi Filsafat Pendidikan Islam Berbasis Manhaj Rasulullah صلى الله عليه وسلم - Pratiwi, Bunga Desti; Ayu Febrianti, Yuliana; Istinwaro, Zulfa; Khoiriyah (JDP (JURNAL DINAMIKA PENDIDIKAN), 2026)
This study stems from the contemporary crisis of education, which is not only academic in nature but also affects the mental health and moral integrity of the younger generation. Recent data indicate a high prevalence of depression, anxiety, academic burnout, and deviant behaviors among adolescents, exacerbated by an educational orientation that focuses solely on achievement and social status, while neglecting character development, meaning in life, and moral integrity. This research aims to: (1) identify the educational strategies of the Prophet Muhammad ﷺ in transforming a jahiliyah society into a civilized one; (2) reconstruct the philosophy of education through the “Curriculum of Life” that he implemented; and (3) explore the foundational philosophy of prophetic education that can be actualized in the context of the era of disruption. The method employed is qualitative–philosophical with a library research design. Primary data are derived from the Qur’an and the Kutub al-Sittah, while secondary data come from national and international journals published within the last five years (2020-2025). Data analysis is conducted through content analysis and hermeneutics to interpret the philosophical meanings of the Prophet’s educational practices.The findings indicate that the prophetic pedagogy of the Prophet Muhammad ﷺ constitutes an educational paradigm grounded in an ontology that views human beings as creatures endowed with fitrah that must be preserved and holistically nurtured. His educational strategies through role modeling (uswah), critical dialogue (hiwar), gradualism (tadarruj), and the use of analogies and parables, integrate the formation of intellect, heart, and character. The reconstruction of educational philosophy through the “Curriculum of Life” affirms that Islamic education unfolds within the realities of life and is based on the synergy of tilawah, tazkiyah, and ta‘lim. Through this process, foundational philosophies tawhid, adab, moral responsibility, and an orientation toward the Hereafter are instilled, giving rise to a generation of Companions who were knowledgeable, virtuous, and empowered. Thus, prophetic pedagogy is not merely a teaching method, but a comprehensive educational system that is relevant for addressing the challenges of education in the modern era of disruption.